How Intellectual Capital Effects Firm’s Financial Performance - Hendra Gunawan; Widya Ramadhani (Journal of Applied Accounting and Taxation, 2018)
This study examined the effect of intellectual capital on the financial performance of the company. Independent variables consisted of structural capital efficiency (SCE), human capital efficiency (HCE), capital employed efficiency (CEE) control variables used in this research are the size and leverage. The population of this study are non-financial companies listed on the Indonesian Stock Exchange (BEI) 2014. Samples were selected using purposive sampling method and obtained 232 companies. This study using simple regression analysis and descriptive statistics for the analysis of the data processed by SPSS 22. Results showed that HCE has negative effect on the financial performance, SCE has significant positive effect on financial performance, and CEE has significant positive effect on financial performance. The limitation in the study is sample that are used only limited to the non-financial sector companies listed on the Indonesia Stock Exchange 2014. Future studies are expected to use other measurements to measure intellectual capital and value of the company, and further research is also expected to increase the research data and select other industrial sectors.